Ex vivo evaluation of a novel cell salvage device to recover canine erythrocytes. Issue 8 (5th September 2022) - Kalmukov, Ivan A.; Galliano, Andrea; Godolphin, Janet; Ferreira, Rui; Cardoso, Ines; Norgate, Daisy J.; Bacon, Nicholas J.
Abstract: Objective: To determine the ability of a cell salvage device to recover canine erythrocytes by direct aspiration of diluted packed red blood cells (pRBC) and saline rinse from blood‐soaked surgical swabs. Study design: Experimental study. Sample population: Twelve recently expired units of canine pRBC. Methods: pRBC units donated from a pet blood bank (after quality analysis) were diluted with anticoagulant, divided into two equal aliquots, and subsequently harvested by direct suction (Su), or soaked into swabs, saline‐rinsed and suctioned (Sw). The volume of product, manual packed cell volume (PCV), and red blood cell mass (rbcM) were measured and compared before and after salvaging. The rbcM recovery was recorded as percentage ([rbcM post salvage]/[rbcM presalvage]x100). Statistical analysis of all measured values was performed (significance p < .05). Results: No difference was detected between pre‐ and post‐salvage PCV or mean rise of PCV for either group. The volume of salvaged blood was 143 ml (SD ± 2.89 ml; Su) and 139.83 ml (SD ± 3.30 ml; Sw), p < .001. The average rbcM recovered was 88.43% (Su) and 84.74%. (Sw) averaged 84.74% ( p = .015). Blood type and order of processing did not influence recovery. Conclusion: The tested cell saver device reliably salvages canine blood in this ex vivo setting. Cell salvage via direct suction produces higher volumes of salvaged blood than rinsing blood‐soaked swabs and salvaging the flush. Clinical significance: Washing blood‐saturated surgical swabs results in a high harvest of red blood cells. The authors recommend it as an adjunct to direct suction to maximize erythrocyte recovery.